Comparative analysis of Insulin‐like growth factor binding protein‐1, placental alpha‐microglobulin‐1, phenol and pH for the diagnosis of preterm premature rupture of membranes between 20 and 36 weeks. Issue 8 (16th May 2019) - Galletta, Marco A. K.; Bittar, Roberto E.; Rodrigues, Agatha S.; Francisco, Rossana P. V.; Zugaib, Marcelo
Abstract: Aim: Preterm premature rupture of membranes (PPROM) is responsible for approximately one‐third of premature births worldwide, and although the diagnosis is often straightforward, this condition can still present difficulties. The purpose of this research was to compare the accuracy of several PPROM diagnostic tests. Methods: A total of 94 pregnant women with clinical suspicion of PPROM who were between 20 and 36 weeks of pregnancy were examined by vaginal speculum, and tests were performed for phenol, pH, insulin‐like growth factor binding protein‐1 (IGFBP‐1) and placental alpha‐microglobulin‐1 (PAMG‐1). All patients were followed up until the diagnosis was fully defined, and a diagnosis of PROM was confirmed by a definitive evolution of the clinical symptoms (visualization of vaginal amniotic fluid or persistence of oligohydramnios). Results: After excluding the cases that could not be definitively diagnosed, a good diagnostic performance of the immunochromatographic tests was observed that was superior to that of the clinical tests. Similar accuracies were observed for IGFBP‐1 (98.7%) and PAMG‐1 (93.9%). However, while the IGFBP‐1 test differed from a vaginal pH ≥7 (88.9%) and the phenol test (85.7%), this did not occur for the PAMG‐1 test. The performance of the tests was modified only by the presence of bleeding (with lower specificity rates for pH and phenol), without interference of gestational age or maternal morbidities. Conclusion: Immunochromatographic tests are good tools but should be used sparingly in resource‐poor settings because they are expensive, and there is no significant difference between PAMG‐1 and traditional tests.